Heterogeneity of human WT1 gene - Ewelina Bielińska (Postępy Higieny i Medycyny Doświadczalnej, 2017)
The WT1 gene, characterized by an extremely complex structure, is located on chromosome 11. It is involved in cell growth and differentiation, and has a strong impact on consecutive stages of the functioning of the body. The WT1 gene may undergo many different mutations, as well as may be overexpressed without a mutation. The molecular basis of diseases such as Wilms tumor, WAGR, Denys-Drash or Frasier syndromes are congenital WT1 mutations, while somatic mutations of this gene occur in acute and chronic myeloid leukemia, myelodysplastic syndrome and also in some other blood neoplasms, as acute lymphoblood leukemia. Increased expression of this gene without its mutation is observed in leukemias and solid tumors. The WT1 may function both as a tumor suppressor gene and as an oncogene. The diversity of WT1 changes causes many controversies, therefore investigations are still carried out to determine the function of this gene, its interaction with other molecules and its prognostic significance in various diseases.